(untitled) (Philosophy and Progress, 2014)
The paper aims to explore the philosophical and sociological foundations of modernity as well as to figure out the pattern of modernity in Bangladesh. Modernity in philosophy refers to the fundamental modification of pre-modern political philosophy of Socrates, Plato and Aristotle by Machiavelli, Copernicus, Kepler, Galileo, Bacon and Newton. Later, in this project, people who employed themselves as original contributors are Hobbes, Rousseau, Locke, Descartes, Spinoza, Leibniz, Kant, Hegel, Schopenhauer, Kierkegaard, Nietzsche, Russell, Heidegger, Popper, Foucault, Derrida, and so on. Amongst these thinkers some were associated to develop the project of modernity based on the Western epistemological and ontological contemplates and some were appeared as the critic of this mundane venture. Modernity, however, in sociology refers to the move from feudal social order to the capitalistic social order under the grand project of industrialization, secularization and rationalization. Modernity, from its commencement, possesses two innate characteristics: one is epistemological or conjectural which is the actual motif of philosophy, and another one is ontological or applied which is congruence to the motif of sociology. Both philosophy and sociology take modernity as a vocation and shared the same epistemological and ontological standpoints. In the context of Bangladesh I tried to explain modernity under the framework of philosophy and sociology as well as conceptualized the pattern of modernity as ?copied because the type of modernity is found here as the simulation of Western and Eastern cultural and social values. DOI: http://dx.doi.org/10.3329/pp.v51i1-2.17682